Hypoglycemia after initiating insulin therapy based on the results of structured self-control and monitoring of blood glucose - A. V. Petrov; L. G. Strongin (Медицинский совет, 2018)
Hypoglycemia detection in T2DM patients is an important issue which is usually accomplished with self-monitoring of blood glucose (SMBG). Optimal schedule of testing and diagnostic threshold are important for effective SMBG. Aims of study: To evaluate hypoglycemia frequency by SMBG using structured AccuChek 360 View protocol and glucose monitoring and increase SMBG efficacy in the detection of hypoglycemia. Study design: 16 T2DM patients after initiation of insulin treatment were included. Each patient had 3 days of glucose monitoring together with SMBG 7 times a day after hospital discharge and 3 months later. Results: Hypoglycemia was detected in 38% of monitoring periods; this patients had higher glucose variability and lower average glucose. SMBG detected hypoglycemia in 16% of periods. 6 out of 7 unrecognized hypoglycemias were during night. This 6 cases were characterized by minimal daytime glucose levels by SMBG below 5 mmol/l. ROC-analysis demonstrated minimal glucose level during daytime of 4.8 mmol/l to have 92% sensitivity and 74% specificity for detection of any hypoglycemia by glucose monitoring. Conclusion: Structured Accu-Chek 360 View SMBG can reliably detect daytime hypoglycemia but regular nighttime testing is recommended in all T2DM patients using insulin for detection of nighttime hypoglycemia. Minimal glucose levels below 4.8-5 mmol/l during daytime corresponds with high hypoglycemia risk.